ANALISIS MUTU PENDIDIKAN ANAK USIA DINI DITINJAU DARI MANAJEMEN SEKOLAH FULL DAY DI RA SYARIFUL HIKAM - Nurhidayah; Muhammad Nofan Zulfahmi (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
Early childhood education includes all activities carried out by parents and educators in an effort to care for, nurture and educate by creating an environmental atmosphere and providing experiences for children to explore through observing, imitating and experimenting by involving all aspects of potential intelligence. The research approach applied is a qualitative method, by verifying data through triangulation techniques. The results of research conducted at RA Syariful Hikam show that the management of RA Syariful Hikam's early childhood education program implements management functions well including planning, implementation, supervision and coaching. At RA Syariful Hikam, education management is carried out in accordance with eight national standards for early childhood education. The effectiveness of the education management implemented by this institution has encouraged the foundation to introduce a full day school program,   a wise solution for parts who work to leave their children at school.